Ilustrasi Digital Bergaya Semi-Realis sebagai Interpretasi Simbolis Lagu-Lagu Blink-182 - Galuh Prasasti; Bangkit Sanjaya (Lembaga Pengembangan Kinerja Dosen, 2026)
Music functions not only as an auditory medium but also as a source of visual interpretation through the process of intersemiotic translation, which enables meanings expressed through lyrics and musical atmosphere to be translated into visual forms. This creative research aimed to produce semi-realistic digital illustrations as symbolic interpretations of three Blink-182 songs, namely